EVALUATION OF LIPID PROFILE OF HYPERTENSIVE PREGNANT WOMEN ATTENDING MGBAKWU PRIMARY HEALTH CARE CENTRE, ANAMBRA STATE (FUDMA JOURNAL OF SCIENCES, 2024)
Hypertension is a serious global public health problem. Serum lipid alteration is a pivotal factor that births hypertension during pregnancy and has been implicated in diverse deleterious health outcomes. Thus, the aim of this study was to evaluate the lipid profiles of hypertensive pregnant women attending Mgbaukwu Primary Health Care (PHC) Centre. A total of 70 pregnant women who had consented were recruited to participate. While thirty five (35) pregnant women were hypertensive, the other remaining 35 pregnant women were not hypertensive (normotensive) and thus, were considered the control group. Socio-demographic characteristics of the participants were generated using structured questionnaire, while lipid profiles of the participants were determined using standard procedures. Results obtained from this study shows that 80% and 34.28% of the hypertensive and normotensive pregnant women respectively were within the age range of 32-37 years old, while 68.6% and 48.57% of the hypertensive and normotensive pregnant women respectively were traders and had completed only secondary school education. The value recorded on Total Cholesterol (TC) , Very Low Density Lipoprotein (VLDL), Low Density Lipoprotein (LDL), and Triglycerol (TG) in Hypertensive Pregnant Women (HYPW) were significantly (p
Keywords: Health; Hypertension; Lipid; Participants; Pregnancy; Women